A Review on Recent Development of Neutro-Topology - Bhimraj Basumatary (Neutrosophic Sets and Systems)
Smarandache proposed NeutroAlgebra and AntiAlgebra. NeutroAlgebras and AntiAlgebras are a new research topic based on real-world scenarios. He investigated the concepts of neutro- and anti-structure. He demonstrated using NeutroAlgebra concepts that just because a statement is completely true in a classical Algebra does not imply that it is also completely true in a NeutroAlgebra or AntiAlgebra. It is determined by the operations and axioms on which it is based (whether they are completely true, partially true, totally false, or partially or completely indeterminate). This study examines the concepts of Generalised regular Neutro-Topological space and its properties.